Sistem Pendeteksi DDoS menggunakan Algoritma CUSUM pada OpenFlow SDN - Mahadika Putra Pratama; Primantara Hari Trisnawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
With the development of technology in today's era, Software Defined Network (SDN) has been used everywhere. SDN separates network control and data fields. SDN has several protocols that are used everywhere, such as OpenFlow SDN. OpenFlow is standardized by the Open Networking Foundation (ONF) to overcome the dynamic nature and high bandwidth of applications and reduce the complexity of system management (Alsaeedi et al., 2019). The separation of the controller from the data plane causes security holes in the data flow such as communication between lines that can be targeted by attackers such as DDoS (Ahmad et al., 2015)â . The algorithm used is the CUSUM algorithm where the CUSUM algorithm has a fairly reliable accuracy point in detecting DDoS attacks. The CUSUM algorithm uses a method called Entropy. Entropy is a random data that occurs because of the abnormality of an event (Ramadhani et al., 2008)â . The implementation of the CUSUM Algorithm on OpenFlow SDN is able to detect attacks with close to high accuracy as much as 80% and a detection time of 1 second.